The triterpenoid curcumene mediates the relative hydrophilicity of Bacillus subtilis spores - Stefany Castaldi; Giuliana Donadio; Ivana Staiano; Ezio Ricca; Rachele Isticato (mBio)
ABSTRACT Spores of Bacillus subtilis are surrounded and protected by the coat and the crust, multi-layered structures mainly made of proteins and polysaccharides. These polysaccharides are covalently linked to some of the coat and crust proteins and influence some spore properties, such as surface adhesion and hydrophilicity. This study reports that a mutant strain lacking the spsA-L operon, encoding 11 enzymes involved in the synthesis of spore surface polysaccharides, produced spores exposing on their surface hydrophobic molecules that were responsible for the drastic reduction of hydrophilicity of the mutant spores. Biochemical and genetic data support the identification of the C35-terpenoid curcumene, a precursor of the spore-associated lipid sporulene, as the highly hydrophobic molecule present on the surface of mutant spores.IMPORTANCEBacterial spores are the most resistant cell forms on Earth. The metabolically quiescent spores withstand conditions that would be lethal for other cells, maintaining the capacity to sense the environment and respond to the presence of favorable conditions by germinating. Such remarkable resistance is also due to the complex layers that surround the spore cytoplasm and protect it against damaging factors. Altogether, the spore surface layers form a complex cell structure composed of proteins, polysaccharides, and, as highlighted by this study, also of lipids. Understanding the complexity of the spore surface and the specific molecules involved in its structure is an essential step for unraveling the mechanisms underlying the spore’s resistance to environmental assaults.